2022
DOI: 10.1155/2022/8141443
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Molecular Mechanism of Tong Xie Yao Fang in Treating Ulcerative Colitis Using Network Pharmacology and Molecular Docking

Abstract: Objective. The purpose of this study was to investigate the mechanisms of action of Tong Xie Yao Fang (TXYF) against ulcerative colitis (UC) by employing a network pharmacology approach. Methods. The network pharmacology approach, including screening of the active ingredients and targets, construction of the active ingredient-drug target network, the active ingredient-diseasetarget network, the protein–protein interaction (PPI) network, enrichment analyses, molecular docking, and targets validation, was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…LPS can trigger the release of inflammatory mediators like PTGS2. [ 28 ] Zuo et al [ 29 ] demonstrated that Cr (VI) induced PTGS2 expression via an NFκB/c-Jun/AP-1-dependent pathway. Therefore, these key targets have significant correlations within important cancer-related cellular processes.…”
Section: Discussionmentioning
confidence: 99%
“…LPS can trigger the release of inflammatory mediators like PTGS2. [ 28 ] Zuo et al [ 29 ] demonstrated that Cr (VI) induced PTGS2 expression via an NFκB/c-Jun/AP-1-dependent pathway. Therefore, these key targets have significant correlations within important cancer-related cellular processes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, network pharmacological analysis has been increasingly applied to TCM research. Network pharmacology can be used to search for the relationships among herbs, active ingredients, diseases and target genes, predict key active ingredients, targets and possible mechanisms of TCM in the treatment of diseases, and provide clues for further research [ 7 , 8 ]. In the present study, network pharmacological methods were used to analyze the potential mechanisms of YQQYJDF in treating GBM.…”
Section: Discussionmentioning
confidence: 99%
“…It uses bioinformatic methods to systematically catalog the molecular interactions of a drug. It is also an effective method of studying the mechanism of TCM prescriptions in treating diseases [ 7 , 8 ]. The present study aimed to use a network pharmacology method to analyze the underlying mechanism of YQQYJDF in treating GBM.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Network pharmacology, used to explain the process of disease occurrence and development from the perspectives of systems biology and biological networks, could be used to elucidate the action of traditional Chinese medicine. 14,15 Molecular docking was a method to calculate the binding affinity between small molecules and specific receptors by calculating and screening active ingredients. 16 Consequently, the investigatory prowess of network pharmacology and molecular docking was harnessed to unravel the efficacious constituents and mechanistic pathways underlying the therapeutic impact of RL in addressing ALI.…”
Section: Introductionmentioning
confidence: 99%